BEATRICE GRIMSHAW’S PROVERB SPLICER AND HER ARTFUL USE OF PROVERBS - Unseth, Peter (Proverbium - Yearbook, 2020)
The neglected Irish-born writer Beatrice Grimshaw (1870-1953) created a character in a novel who spliced English language proverbs. Putting such spliced proverbs into his mouth, Grimshaw both developed the character and inserted some bright spots of humor into the novel. Patrick O’Brian has created a proverb-splicing character that has attracted scholarly attention in his novels, but Grimshaw’s use of this technique predated his by about 60 years. Grimshaw also used proverbs in other artful ways.